The meiotic checkpoint monitoring synapsis eliminates spermatocytes via p53-independent apoptosis - ODORISIO, T; RODRIGUEZ, T. A; EVANS, E. P; CLARKE, A. R; BURGOYNE, P. S (Nature genetics, 1998)
Evidence is accumulating that meiosis is subject to 'checkpoints' that monitor the quality of this complex process. In yeast, unresolved double strand breaks (DSBs) in DNA are thought to trigger a 'recombination checkpoint' that leads to pachytene arrest. In higher eukaryotes, there is evidence for a checkpoint that monitors chromosome synapsis and in mammals the most compelling evidence relates to the sex chromosomes. In normal male mice, there is synapsis between the X and Y pseudoautosomal regions; in XSxr(a)O mice, with a single asynaptic sex chromosome, there is arrest at the first meiotic metaphase, the arrested cells being eliminated by apoptosis (our unpublished data). Satisfying the requirement for pseudoautosomal synapsis by providing a pairing partner for the XSxr(a) chromosome avoids this arrest. We have considered that this 'synapsis checkpoint' may be a modification of the yeast 'recombination checkpoint' with unresolved DSBs (a corollary of asynapsis) providing the trigger for apoptosis. DSBs induced by irradiation are known to trigger apoptosis in a number of cell types via a p53-dependent pathway, and we now show that irradiation-induced spermatogonial apoptosis is also p53-dependent. In contrast, the apoptotic elimination of spermatocytes with synaptic errors proved to be p53-independent.